2021
DOI: 10.1111/lam.13422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the probiotic and functional potential of Lactobacillus agilis 32 isolated from pig manure

Abstract: Escherichia coli is a symbiotic bacterium in humans and animals and an important pathogen of humans and animals. Prevention and suppression of E. coli infection is of great concern. In this study, we isolated a strain of Lactobacillus agilis 32 from pig manure and evaluated its biological characteristics, and found that its bacterial survival rate was 25% after 4 h of treatment at pH 2, and under the condition of 0·5% bile concentration, its survival rate exceeds 30%. In addition, L. agilis 32 has a cell surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…In our study, the strong bacteriostatic activity of L. salivarius supernatant and L. agilis supernatant were verified. In agreement, L. salivarius and L. agilis 32 were previously proved to present an excellent antibacterial effect on pathogenic bacterium of humans or chickens ( 25 , 30 ). These implied that the stimulation from gut flora to ISCs was alleviated after feeding L. salivarius or L. agilis .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our study, the strong bacteriostatic activity of L. salivarius supernatant and L. agilis supernatant were verified. In agreement, L. salivarius and L. agilis 32 were previously proved to present an excellent antibacterial effect on pathogenic bacterium of humans or chickens ( 25 , 30 ). These implied that the stimulation from gut flora to ISCs was alleviated after feeding L. salivarius or L. agilis .…”
Section: Discussionsupporting
confidence: 63%
“…Concerning L. salivarius or L. agilis , Xia et al ( 24 ) pointed out that the colonization of L. salivarius LI01 in rats would produce indole-3-lactic acid and enhance arginine metabolism in the intestine, exerting an effect on energy accumulation in the liver. Shi et al ( 25 ) suggested that L. agilis 32 was tolerant to the gastrointestinal environment of chicken and processed an excellent antibacterial effect on E. coli 10, primarily related to its metabolites or low pH conditions. Recently, intestinal microbes derived succinate was demonstrated to induce tuft cell expansion by increasing the TCA cycle (tricarboxylic acid cycle), thus further reducing inflammation in mice’s Crohn’s-like ileitis ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along the grain-feed chain, a strain of Lig . agilis was isolated from pig manure and showed promising probiotic potential [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results showed that there was a significant difference in beta diversity between DON and DBZN groups, which means that dietary BZN in DON-contaminated diets changed the intestinal microbiota structure of piglet. Heatmaps showed that Lactobacillus ruminis and Lactobacillus agilis were enriched in the DBZN group, and they were able to inhibit Escherichia coli, which means BZN may treat intestinal pathogen infection (50,51). PICRUST showed that the dietary BZN supplementation in DON-contaminated diet enriched peptidases pathway and dietary BZN supplementation in basal diet-enriched secretion system and bacterial mobility protein pathway.…”
Section: Discussionmentioning
confidence: 99%